The vulnerability of the peninsulas toward the manifestations of territorial-political conflicts - Сливка, Роман (Human Geography Journal, 2019)
In the early 21st century, conflicts remained widespread on the political map of the world. The article explores the role of the peninsula as a subject of territorial dispute, territorial expansion, as well as the region of arms deployment and battlefield. A significant challenge to the security of Ukraine and all of Central and Eastern Europe was the annexation of Crimea by Russia in 2014. Despite the popular in modern Political Geography discourse on the decline of traditional Geopolitics, the peninsulas still can be explored as vulnerable to manifestations of geopolitical and military rivalry. The purpose of the article is to establish a list of peninsulas vulnerable to the manifestation of international territorial claims, disputes and conflicts, and on this basis to propose a classification of peninsular regions according to their position on the political map. The peninsula is a stretch of land that can be functionally used to establish military and civilian control of adjacent territories. Maintaining military bases on the peninsula makes sense to modern nations because of their role as outposts for the effective deployment of land, air, and naval components of the armed forces and their use inland, adjacent regions and airspace. The peninsulas became a battlefields during the so-called proxy wars that took place between the countries of the West and the East on the territory of third countries. The conquest and decolonization of the peninsula have given rise to specific forms of jurisdiction, such as the British Overseas Territory of Gibraltar, with its autonomous system of government within the United Kingdom, or the autonomous Hong Kong and Hong Kong. The large peninsulas are characterized by several historic cores of statehood, some of which may be located outside the state. This creates favorable conditions for regionalism and devolution (Lombardy in Italy), separatism (Catalonia in Spain), irredentism (Crimea, Bakassi) and armed conflicts (Somalia). The Russian annexation of the Crimean Peninsula is a flagrant violation of international law. De-occupation is the only acceptable solution to the problem, but the necessary prerequisites for changing the political regime and paradigm of the foreign policy of the Russian Federation must be ripe for this.